Canine infection with Borrelia burgdorferi, Dirofilaria immitis, Anaplasma spp. and Ehrlichia spp. in Canada, 2013–2014 - Brian H. Herrin; Andrew S. Peregrine; Jonas Goring; Melissa J. Beall; Susan E. Little (Parasites & Vectors, 2017)
Abstract Background Canine test results generated by veterinarians throughout Canada from 2013–2014 were evaluated to assess the geographical distribution of canine infection with Borrelia burgdorferi, Dirofilaria immitis, Ehrlichia spp., and Anaplasma spp. Methods The percent positive test results of 115,636 SNAP® 4Dx® Plus tests from dogs tested were collated by province and municipality to determine the distribution of these vector-borne infections in Canada. Results A total of 2,844/115,636 (2.5%) dogs tested positive for antibody to B. burgdorferi. In contrast, positive test results for D. immitis antigen and antibodies to Ehrlichia spp. and Anaplasma spp. were low, with less than 0.5% of dogs testing positive for any one of these three agents nationwide. Provincial seroprevalence for antibodies to B. burgdorferi ranged from 0.5% (Saskatchewan)–15.7% (Nova Scotia); the areas of highest percent positive test results were in proximity to regions in the USA considered endemic for Lyme borreliosis, including Nova Scotia (15.7%) and Eastern Ontario (5.1%). These high endemic foci, which had significantly higher percent positive test results than the rest of the nation (P < 0.0001), were surrounded by areas of moderate to low seroprevalence in New Brunswick (3.7%), Quebec (2.8%), and the rest of Ontario (0.9%), as well as northward and westward through Manitoba (2.4%) and Saskatchewan (0.5%). Insufficient results were available from the westernmost provinces, including Alberta and British Columbia, to allow analysis. Conclusion Increased surveillance of these vector-borne disease agents, especially B. burgdorferi, is important as climate, vector range, and habitat continues to change throughout Canada. Using dogs as sentinels for these pathogens can aid in recognition of the public and veterinary health threat that each pose.